Monitoring aerobic capacity in cancer survivors using self-reported questionnaires: criterion validity and responsiveness - Anouk T.R. Weemaes; Renske Meijer; Milou Beelen; Martijn van Hooff; Matty P. Weijenberg; Antoine F. Lenssen; Lonneke V. van de Poll-Franse; Hans H.C.M. Savelberg; Goof Schep (SpringerOpen, 2023)
Abstract Background Evaluating the criterion validity and responsiveness of the self-reported FitMáx©-questionnaire, Duke Activity Status Index (DASI) and Veterans Specific Activity Questionnaire (VSAQ) to monitor aerobic capacity in cancer survivors. Methods Cancer survivors participating in a 10-week supervised exercise program were included. The FitMáx©-questionnaire, DASI, VSAQ and a cardiopulmonary exercise test (CPET) were completed before (T0) and after (T1) the program. Intraclass correlation coefficients (ICC) were calculated between VO2peak estimated by the questionnaires (questionnaire-VO2peak) and VO2peak measured during CPET (CPET-VO2peak), at T0 to examine criterion validity, and between changes in questionnaire-VO2peak and CPET-VO2peak (ΔT0-T1) to determine responsiveness. Receiver operating characteristic (ROC) analyses were performed to examine the ability of the questionnaires to detect true improvements (≥ 6%) in CPET-VO2peak. Results Seventy participants were included. Outcomes at T1 were available for 58 participants (83%). Mean CPET-VO2peak significantly improved at T1 (Δ1.6 mL·kg− 1·min− 1 or 8%). Agreement between questionnaire-VO2peak and CPET-VO2peak at T0 was moderate for the FitMáx©-questionnaire (ICC = 0.69) and VSAQ (ICC = 0.53), and poor for DASI (ICC = 0.36). Poor agreement was found between ΔCPET-VO2peak and Δquestionnaire-VO2peak for all questionnaires (ICC 0.43, 0.19 and 0.18 for the FitMáx©-questionnaire, VSAQ and DASI, respectively). ROC analysis showed that the FitMáx©-questionnaire was able to detect improvements in CPET-VO2peak (area under the curve, AUC = 0.77), when using a cut-off value of 1.0 mL·kg− 1·min− 1, while VSAQ (AUC = 0.66) and DASI (AUC = 0.64) could not. Conclusion The self-reported FitMáx©-questionnaire has sufficient validity to estimate aerobic capacity in cancer survivors at group level. The responsiveness of the FitMáx©-questionnaire for absolute change is limited, but the questionnaire is able to detect whether aerobic capacity improved. The FitMáx©-questionnaire showed substantial better values of validity and responsiveness compared to DASI and VSAQ.